Green Pathway for Processing Non-mulberry Antheraea pernyi Silk Fibroin/Chitin-Based Sponges: Biophysical and Biochemical Characterization - Silva, Simone S.; Gomes, Joana M.; Vale, Ana Catarina; Lu, Shenzhou; Reis, Rui L.; Kundu, Subhas C. (Frontiers in Materials, 2020)
Silk protein fibroin (SF)-based matrices from nonmulberry, and mulberry silkworms have been used for different applications in regenerative medicine. Silk fiber spun by the wild nonmulberry silkworm Antheraea pernyi (Ap) is also a promising biomedical material, due to the presence of the inherent tripeptide sequence of Arginine-Glycine-Aspartic acid (RGD) on the protein fibroin sequences. However, SF derived from the Ap cocoons still lack exploitation in the healthcare field due to its poor solubility in the conventional solvents. This work addresses the application of green chemistry principles, namely the use of ionic liquids (ILs, 1-butyl-imidazolium acetate) and renewable resources such as Antheraea pernyi silk fibroin (ApSF) and chitin (Ch), for the fabrication of sponges from the blends of ApSF and Ch (APC). The formation of -sheet in different contents during ApSF/Ch/IL was acquired by exposing gels to methanol/water and ethanol/water. The sponges were then obtained by freeze-drying. This approach promotes the formation of both stable and ordered ApSF/Ch-based sponges. The developed sponges presented suitable porosity and interconnectivity, appreciable swelling degree, and tuneable viscoelastic compressive properties for tissue engineering applications. Collectively, the structural properties of these ApSF/Ch-based sponges make them promising candidates for biomedical applications, namely cartilage regeneration.